Examining the normative and persuasive effects of televised U.S. Senate debates. (2nd January 2021) - Bramlett, Josh C.
Abstract: Televised political debates are largely studied at the presidential level, and there is a paucity of research on debate effects for nonpresidential campaigns. This study explored televised debate effects in the context of the 2018 U.S. midterm Senate elections. A pretest/posttest design tested the normative and persuasive outcomes of debate viewing. Viewing one of the two Senate debates promoted information acquisition, influenced attitudes such as political information efficacy, candidate evaluations, intention to vote for a candidate, and intention to vote in the midterm elections, and had marginal influences on political cynicism and political interest. Presidential debates are not the only debates that matter: nonpresidential televised debates can also persuade voters and foster positive democratic outcomes.